Answer:
A
Step-by-step explanation:
f(g(3)= f(g(x=3)) = f(
) = f(4/2) = f(2) = f(x=2) = 3*2-7 = 6-7 = -1
Answer:
No solution
Step-by-step explanation:
So first we have to Distribute;
-3x + 3 > -3x - 2
This is an solution which means that they can never intersect on a graph.
We can solve further if you want;
Add 3x to both sides;
The x cancel themselves out.
3 > -2
Answer:
6
Step-by-step explanation:
Yeah, x= 7/2 and y= -5/2
Please mark as brainliest and I hope this helps
-----------------
0.04m² - n²
(0.2m)² - n²
<span>(0.2m + n)(0.2m - n)</span>
-----------------